The novelty of complementarity between trans regionalism and new bilateralism: Southeast Asia–middle east affairs - Gürol Baba; Yew Meng Lai (Project MUSE, 2025)
Trans regionalism entails non-institutional, flexible cooperation across regions, contrasting with the more structured, rule-based approach of interracialism. New bilateralism, which emerged after the Cold War, extends beyond economic governance to incorporate strategic, security, and cultural interactions, bypassing institutional constraints. This research aims to clarify the conceptual and practical complementarity of these two concepts and their significance in Middle Eastern and Southeast Asian interactions. Both regions possess dynamic actors, including Türkiye, Saudi Arabia, Iran, Malaysia, Indonesia, and Singapore, yet the distribution of intra-regional power remains uneven. Additionally, the regional organizations in both regions lack strong institutional frameworks. The study highlights that despite weak regional organizations and the uneven capabilities among intra-regional actors, trans regionalism with new bilateralism offers effective platforms for region-to-region cooperation. These eclectic arrangements favor flexibility over institutionalization, enabling small and middle powers to engage in issue-specific collaborations free from the dominance of great powers while also incorporating non-state actors. This conceptual and practical nexus is particularly pertinent in today's global political landscape, where formal institutions often fall short, and agile, ad-hoc arrangements are better suited to addressing the complexities of international relations.